2016
DOI: 10.1101/lm.040360.115
|View full text |Cite
|
Sign up to set email alerts
|

Preexposure to salty and sour taste enhances conditioned taste aversion to novel sucrose

Abstract: Conditioned taste aversion (CTA) is an intensively studied single-trial learning paradigm whereby animals are trained to avoid a taste that has been paired with malaise. Many factors influence the strength of aversion learning; prominently studied among these is taste novelty-the fact that preexposure to the taste conditioned stimulus (CS) reduces its associability. The effect of exposure to tastes other than the CS has, in contrast, received little investigation. Here, we exposed rats to sodium chloride (N) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 45 publications
3
39
1
Order By: Relevance
“…We have recently begun an inquiry into this topic (Flores et al 2016), showing that experience with salty and sour tastes (hereafter "taste preexposure" or TPE) enhances aversions toward a novel taste; experience with both tastes is more effective than experience with either alone, and three sessions of TPE is more effective than two. These results, which contrast with both classic interference effects that reduce conditioning strength (Pavlov 1927;Bouton 1993; Kwok et al 2012) and the above-mentioned effects that occur across an entirely different time scale (Riege 1971;Donato et al 2013;Leger et al 2015), demonstrate that benign experience with one set of tastes over two to three days can impact the strength of learning established in a later associative conditioning paradigm using a different taste.…”
mentioning
confidence: 99%
“…We have recently begun an inquiry into this topic (Flores et al 2016), showing that experience with salty and sour tastes (hereafter "taste preexposure" or TPE) enhances aversions toward a novel taste; experience with both tastes is more effective than experience with either alone, and three sessions of TPE is more effective than two. These results, which contrast with both classic interference effects that reduce conditioning strength (Pavlov 1927;Bouton 1993; Kwok et al 2012) and the above-mentioned effects that occur across an entirely different time scale (Riege 1971;Donato et al 2013;Leger et al 2015), demonstrate that benign experience with one set of tastes over two to three days can impact the strength of learning established in a later associative conditioning paradigm using a different taste.…”
mentioning
confidence: 99%
“…It is important to note that to assess taste perception and memory formation while disregarding neophobia requires the usage of a taste that minimizes the neophobic reaction. This was our reason for choosing sucrose, which evokes only minor neophobic responses (Miller and Holzman, 1981; Franchina and Gilley, 1986; Franchina and Slank, 1988; Flores et al, 2016), as opposed to saccharin (Domjan and Gillan, 1976; Lin et al, 2012a). This choice, however, prevented us from exploring the relation between BLA epochal activity and neophobic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…While rats exhibit pronounced neophobia to foods, neophobia to novel tastes is more varied (Miller and Holzman, 1981). Previous studies have shown that taste neophobia is dependent upon certain tastes and can vary with concentration (Flores et al, 2016; Monk et al, 2014); however, neophobia is rarely observed with sucrose (Miller and Holzman, 1981). Furthermore, the post-ingestive effects of pairing an odor with calorically-rich sucrose, compared to a non-caloric taste, induces stronger odor-taste associations (Bonacchi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%